2020
DOI: 10.3390/app10144998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Design Formulations and Numerical Results for In-Plane FRCM-Strengthened Masonry Walls

Abstract: Strengthening strategies and structural rehabilitation of existing buildings with innovative materials and techniques are today one of the main activities in the field of structural engineering. Externally bonded Fiber Reinforced Cementitious Matrix (FRCM), materials are spreading as an alternative strengthening technique to the more traditional Fiber Reinforced Polymer (FRP) ones, especially for masonry elements. This research focuses on the assessment of the shear strength of in-plane FRCM-strengthened mason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The stress redistribution occurring in the specimen in the non-linear range does not affect the value of the maximum principal stress, σ I (the tensile stress in Appendix A), computed with the linear elastic solution [58]. For this reason and for the discussion on the interpretation of the diagonal compression test in Appendix A, Equation (A26) will provide the values of the diagonal tensile strength later in this document, as in References [40,41,[59][60][61]:…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress redistribution occurring in the specimen in the non-linear range does not affect the value of the maximum principal stress, σ I (the tensile stress in Appendix A), computed with the linear elastic solution [58]. For this reason and for the discussion on the interpretation of the diagonal compression test in Appendix A, Equation (A26) will provide the values of the diagonal tensile strength later in this document, as in References [40,41,[59][60][61]:…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The second method is easier to perform than the shear-compression test [41]. It consists of loading one diagonal of a square masonry wall in compression, until failure, which usually involves the formation of cracks along the loaded diagonal.…”
Section: Experimental Programmentioning
confidence: 99%
“…The results are compared in terms of diagonal load at the varying displacements (or strains) along the panel diagonals, monitored along almost their whole length or, occasionally, focusing on a more restricted central portion [8,23,27,[32][33][34]. The results can also be reported in terms of calculated shear stress at the varying shear strain, but these outcomes are affected by the different interpretations given to the tests and, in particular, to the assumed stress state at the panel center, which is still an open issue, as evidenced by several authors [28,32,[35][36][37]. Most of the diagonal-compression experimental tests available in the literature on TRM-strengthened masonry focused on a single leaf, clay solid brick masonry; however, some authors tested also panels made of tuff [8,23,27,32,33,38], hollow bricks [17], stones [18,24,25,30] and multiple leaves or infill clay brick masonry [19,24,26,29].…”
Section: In-plane Loadingmentioning
confidence: 99%
“…The results are compared in terms of diagonal load at the varying displacements (or strains) along the panel diagonals, monitored along almost their whole length or, occasionally, focusing on a more restricted central portion [8,23,27,[32][33][34]. The results can also be reported in terms of calculated shear stress at the varying shear strain, but these outcomes are affected by the different interpretations given to the tests and, in particular, to the assumed stress state at the panel center, which is still an open issue, as evidenced by several authors [28,32,[35][36][37].…”
Section: In-plane Loadingmentioning
confidence: 99%
“…Indeed, cementitious matrices offer better performance under elevated temperatures and better compatibility with modern masonry substrates. In fact, several authors observed good performances in practical applications [14][15][16][17][18][19]. More studies, however, are required to better understand the behavior of composite material on the structural response of strengthened masonry elements [20][21][22], both in terms of flexural [23][24][25] and shear performance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%